2015
DOI: 10.1007/s00442-015-3359-6
|View full text |Cite
|
Sign up to set email alerts
|

Root depth and morphology in response to soil drought: comparing ecological groups along the secondary succession in a tropical dry forest

Abstract: Root growth and morphology may play a core role in species-niche partitioning in highly diverse communities, especially along gradients of drought risk, such as that created along the secondary succession of tropical dry forests. We experimentally tested whether root foraging capacity, especially at depth, decreases from early successional species to old-growth forest species. We also tested for a trade-off between two mechanisms for delaying desiccation, the capacity to forage deeper in the soil and the capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 43 publications
1
52
1
2
Order By: Relevance
“…Although there was no difference on fine root B/N ratio between forests dominated by early (such as Betula , Pinus , and Populus ) and late successional genera (such as Fagus , Picea , and Quercus ) in this analysis (Table ), fine root B/N ratio of late‐ uccessional forests were closely aligned with climate, topography, and stand factors (Table ). These results are in accordance with many other studies that indicated that successional status strongly influence fine root dynamics and resource acquisition strategies (Paz et al, ; Yuan & Chen, ). Therefore, we conclude that aboveground variables such as stand density, tree age, and successional status should be included in large‐scale studies in order to improve usefulness of fine root biomass and necromass data.…”
Section: Discussionsupporting
confidence: 93%
“…Although there was no difference on fine root B/N ratio between forests dominated by early (such as Betula , Pinus , and Populus ) and late successional genera (such as Fagus , Picea , and Quercus ) in this analysis (Table ), fine root B/N ratio of late‐ uccessional forests were closely aligned with climate, topography, and stand factors (Table ). These results are in accordance with many other studies that indicated that successional status strongly influence fine root dynamics and resource acquisition strategies (Paz et al, ; Yuan & Chen, ). Therefore, we conclude that aboveground variables such as stand density, tree age, and successional status should be included in large‐scale studies in order to improve usefulness of fine root biomass and necromass data.…”
Section: Discussionsupporting
confidence: 93%
“…Shade-tolerant (usually late-successional) species with high wood density are slow growing and may have lower nutrient requirements and, therefore, allocate less C to traits such as root length and surface area leading to lower root biomass (Xiang et al 2013). In addition, shade-tolerant species may increase nutrient uptake efficiency by producing roots with high SRL and SRA values (Xiang et al 2013, Paz et al 2015. On the other hand, shade-tolerant species may produce roots of low SRL and SRA as a conservative strategy to coexist with other species (Leuschner et al 2009, Xiang et al 2013, Reich 2014, Zangaro et al 2014, which is inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 96%
“…, Paz et al . ). On the other hand, shade‐tolerant species may produce roots of low SRL and SRA as a conservative strategy to coexist with other species (Leuschner et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations